Indonesian Defence Diplomacy: France as A Partner in Military Defence Revitalization during 2019-2023 - Yesi Riana Yusnita Sari (Universitas Muhammadiyah Malang, 2023)
Having a strategic location between two continents (Asia and Australia) and two oceans (the Pacific and the Indian) gives Indonesia the benefit of becoming a leading actor in the region, especially within the ASEAN. However, this geographical location also poses potential threats for Indonesia, both traditional and non-traditional threats. This situation is made worse by the tension between two great powers in the Indo-Pacific: China and the US. Indonesia then needs to have a good military endurance capability, and even though the Indonesian Armed Forces’ personnel is not lacking, the total number of Indonesia’s military equipment is somewhat lacking. Understanding the challenge, Indonesia has been trying to modernize its weapon system by conducting military diplomacy to obtain the best cooperation in weapon system. Therefore, this paper will analyze Indonesia’s effort in defense diplomacy within the period of 2019 - 2023 and how France becomes a partner in the defense sector, by using the Military Diplomacy Approach, as well as analyzing the benefits and challenges of every step that has been taken so far.